2015
DOI: 10.3109/10428194.2014.966242
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and prognostic relevance of CD30 expression in post-transplant lymphoproliferative disorders

Abstract: Post-transplant lymphoproliferative disorders (PTLDs) are potentially fatal, often Epstein-Barr virus (EBV)-driven neoplasias developing in immunocompromised hosts. Initial treatment usually consists of a reduction in immunosuppressive therapy and/or rituximab with or without chemotherapy. However, patients who relapse do poorly, and new treatment options are warranted. With the introduction of the immunoconjugate brentuximab vedotin, the CD30 antigen has become an effectively targetable molecule. Therefore, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 27 publications
3
21
2
Order By: Relevance
“…The early occurrence is in accordance with its higher risk in the first year after solid organ transplantation [12]. This type of PTLD may be CD30+ [13], theoretically with potential therapeutic implications [14]. …”
Section: Discussionmentioning
confidence: 72%
“…The early occurrence is in accordance with its higher risk in the first year after solid organ transplantation [12]. This type of PTLD may be CD30+ [13], theoretically with potential therapeutic implications [14]. …”
Section: Discussionmentioning
confidence: 72%
“…Furthermore, hierarchical clustering of the 100 most strongly regulated DEGs grouped the mice according to their experimental conditions, indicating distinct gene transcription patterns in the B cells from the four different groups (S5 Fig). Genes previously associated with EBV infection of B cells CD28 [29] and CXCL10 [30,31] were up-regulated in EBV-infected groups, whereas the PTLD-associated transcripts IL6 [25] and TNFSFR8 (CD30) [32] were upregulated specifically in the B cells from EBV-infected FK506-treated animals ( Fig 4C).…”
Section: Plos Pathogensmentioning
confidence: 78%
“…One study showed five of nine cases of hairy cell leukemia were positive for cytoplasmic TIA-1, with a small, dot-like, granular expression pattern, while 94 B-cell lymphomas of other types were negative for TIA-1. Based on these findings, TIA-1 reactivity in lymphomas does not necessarily indicate a T-or NK-cell derivation [11]. Neoplastic cells in 13.7% of stage-IIIB/IV Hodgkin's lymphoma also showed expression of TIA-1 [12].…”
Section: Discussionmentioning
confidence: 93%